Adapting Self-Report Measures of Mental Health for Children with Intellectual Disability. Issue 1 (2nd January 2022) - Gilmore, Linda; Campbell, Marilyn; Shochet, Ian
ABSTRACT: Self-report is seen as important in assessments of psychopathology but individuals with intellectual disability may have difficulty with standard questionnaires. This paper reports on the administration and subsequent modifications to several established self-report measures of mental health. Methods : The participants were 57 children with intellectual disability aged 10 to 13 years. They completed the Children's Depression Inventory, Revised Children's Manifest Anxiety Scale, Strengths and Difficulties Questionnaire, Intellectual Disability Mood Scale, and Moods and Feelings Questionnaire. Results : Difficulties with the instruments were identified, including complex wording and item structure, ambiguity and working memory demands. Adaptations were made to the instruments and administration procedures. In a second administration there were improvements in children's ability to respond. The modified questionnaires demonstrated acceptable to good internal consistency and were strongly correlated. Conclusions : Self-report measures of mental health can be completed by children with intellectual disability but may need pilot testing and modifications to make them more appropriate for this population.